PENGARUH MEDIA SOSIAL, WORD OF MOUTH, DAN EFEKTIVITAS IKLAN TERHADAP MINAT BELI PADA TEH GELAS DI KOTA BATAM - Sitompul, Nova Julianti Br; Husda, Nur Elfi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The rise of technology and social media has transformed product promotion and marketing in the digital era. Social media, word of mouth (WOM), and advertising effectiveness significantly influence consumer buying interest. This study examines their impact on buying interest in Teh Gelas products in Batam City using a quantitative descriptive approach. With a sample size of 100 respondents determined via the Lameshow formula, the study targeted Teh Gelas consumers who had tried the product at least once in 2023. Data was collected through an online questionnaire and analyzed using SPSS. Results indicate that social media, WOM, and advertising effectiveness each positively and significantly affect buying interest in Teh Gelas.